Negative workplace behavior and coping strategies among nurses: A cross‐sectional study - Hawkins, Natasha; Jeong, Sarah; Smith, Tony (Nursing & health sciences, 2021)
Negative workplace behavior affecting nurses is an internationally recognized problem. This study examines the types and extent of negative workplace behavior experienced by nurses in non‐metropolitan, regional acute care settings and their ways of coping when subject to that behavior. A cross‐sectional study was conducted involving 74 nurse participants in four regional hospitals in Australia. The structured questionnaire consisted of four parts: demographic questions, the Negative Acts Questionnaire – Revised, questions on exposure to bullying and/or incivility and policy awareness and use of pathways, and the Ways of Coping Questionnaire. Overall, 34% of participants were exposed to bullying and 49% to incivility over the previous month. The most common type of negative workplace behavior reported was “work‐related bullying,” which included exposure to excessive workloads, unrealistic deadlines, and information being withheld. Nurses reported the use of a variety of coping mechanisms, including problem‐focused coping strategies and seeking social support. The findings imply that negative workplace behaviors occur not only at individual nursesʼ level but also derive from the broader contexts of organizational management and systemic factors.